A study of war weariness theory: empirical test for perception of war weariness - Lew, San Hong (Nanyang Technological University, 2023)
War weariness theory posits that war is costly and hence a war-wearied state restrains from future war. The paradox is that this theory has been consistently rejected by quantitative findings when applied on a state level. Yet, scholars find the validity of the theory in prominent case studies (e.g., the United States foreign policy). I argue that the war weariness theory does not always hold true, because the theory is one-dimensional. Current literature assumes war weariness to strictly affect decision-making domestically. However, its impact towards the international audience is overlooked by scholars. I coin the role of war weariness in the eyes of international observers as the perception of war weariness. This perception, through the lens of rationalist explanation of war, serves as key public information in learning other states’ private resolve and capabilities. This paper finds statistical evidence that a higher degree of perception of war weariness invites more challenges and thus weakens general deterrence. The empirical findings support an alternative explanation for the paradox of war weariness: a state’s war weariness implies vulnerability in the eyes of international actors and incentivises belligerence from other states. The findings also have implications for proxy wars in the global arena.